Effects of Covid-19 confinement on the mental health of children and adolescents in Spain - Juan Pablo Pizarro-Ruiz (Nature Portfolio, 2021)
Abstract In Spain, in order to control COVID-19 transmission, one of the strictest confinement measures in the world for children and teenagers has been implemented. From 14 March to 26 April 2020 underage Spaniards were not allowed to leave their homes, except for reasons of force majeure. This could have consequences on their mental health in both the short and the long term. Thus, the aim of the present study was to explore the consequences of confinement on the mental health of Spanish children and teenagers, at the time when minors had been locked down in their homes between 8 and 10 days. The sample was composed of 590 confined Spanish children and teenagers between 8 and 18 years old. The scales of Depression, Self-esteem, Anxiety, Problems with Emotional Regulation, Rage Control Problems, Integration and Social Competence, Somatic Complaints, Rebellious Behaviour, as well as Awareness of the Problems of the Assessment System for Children and Adolescents (SENA) were used. The results revealed that, during confinement, children and adolescents showed emotional and behavioural alterations. This study, as far as we know, is the first one to explore the psychological consequences of lockdown in minors while it was taking place, with them being the ones directly assessed.